1995
DOI: 10.1007/bf00186787
|View full text |Cite
|
Sign up to set email alerts
|

Eye primordium transplantation in Xenopus embryo

Abstract: A part of the eye primordium, the presumptive retinal anlage, was transplanted from stage-23/24 Xenopus boreatis to replace the removed olfactory anlage of Xenopus laevis. Cells of the two species can be distinguished under fluorescence microscopy, and we used the resulting chimeras to determine whether the transplanted eye primordium would inhibit the regeneration of the olfactory anlage, whether it would connect with its usual target, the diencephalon, and whether migration of cells would occur from the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Prior work showed that ectopic eyes induced in the cranial region of tadpoles extended cellular bridges and axons towards the optic tecta and were maintained through metamorphosis (Harris, 1986;Koo and Graziadei, 1995;Sedohara et al, 2003). When ectopic eyes were transplanted just behind the head along the dorsal midline, axons from transplanted eyes appeared to enter the spinal cord (Giorgi and Van der Loos, 1978;Katz and Lasek, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work showed that ectopic eyes induced in the cranial region of tadpoles extended cellular bridges and axons towards the optic tecta and were maintained through metamorphosis (Harris, 1986;Koo and Graziadei, 1995;Sedohara et al, 2003). When ectopic eyes were transplanted just behind the head along the dorsal midline, axons from transplanted eyes appeared to enter the spinal cord (Giorgi and Van der Loos, 1978;Katz and Lasek, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Xenopus has been successfully used to analyze eye development, with well-documented pathways for eye induction, lens formation, retinal pathfinding and vascularization (Holt, 1984;Henry and Grainger, 1990;Chien et al, 1993;Hirsch and Harris, 1997;Kenyon et al, 1999;Lupo et al, 2005). In addition, studies have reported the generation of ectopic eyes in tadpoles through surgical techniques, and more recently through embryonic microinjection of a number of 'eye control genes' including Pax6, Rx1, Otx2 and Six3 (Koo and Graziadei, 1995;Chow et al, 1999;Ohuchi et al, 1999;Ashery-Padan and Gruss, 2001;Kenyon et al, 2001;Sedohara et al, 2003;Bailey et al, 2004), as well as through modulation of bioelectrical determinants of organ identity (Pai et al, 2012). Ectopic eyes induced in the cranial region of tadpoles appear to extend 'cellular bridges' and axons towards the optic tecta of the host and these structures are maintained across metamorphosis into adulthood (Harris, 1986;Koo and Graziadei, 1995;Sedohara et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, positional information plays a large role in the patterning behavior not only of single cells and tissues; examples of position-dependent remodeling will be discussed below in the context of deer antler damage and amphibian blastema transplant experiments. Even position along the left-right axis is remembered: when eyes are transplanted, the optic axon fibers penetrate the host’s diencephalon on the side from which the eye was removed from the donor (Koo and Graziadei, 1995)!…”
Section: What Information Do Morphogenetic Fields Carry?mentioning
confidence: 99%
“…Insight may be gained from a number of studies in which researchers create morphologically complete ectopic eyes in vertebrates through the transplantation of developing eye primordia [ 15 19 ], misexpression of a master eye control genes, including Otx2 , Pax6 , Rx1 , and Six3 [ 20 25 ], or establishment of eye-specific bioelectrical states in embryonic tissues [ 9 ]. Cellular tracking revealed that in some cases the retinal ganglion cells of ectopic eyes penetrated the host, growing toward the brain or spinal cord [ 16 , 26 ], though the signals guiding the transplanted neurons have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%